2023
DOI: 10.3390/brainsci13020265
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity Evaluation of Resting-State Brain Networks in Alzheimer’s Disease, Amnestic Mild Cognitive Impairment, and Normal Aging: An Exploratory Study

Abstract: (1) Background: Alzheimer’s disease (AD) is a neurodegenerative disease with a high prevalence. Despite the cognitive tests to diagnose AD, there are pitfalls in early diagnosis. Brain deposition of pathological markers of AD can affect the direction and intensity of the signaling. The study of effective connectivity allows the evaluation of intensity flow and signaling pathways in functional regions, even in the early stage, known as amnestic mild cognitive impairment (aMCI). (2) Methods: 16 aMCI, 13 AD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Wu et al [48] found similar results using group information-guided ICA, showing that rs-FC alterations mostly appear in the temporal, cingulate, and angular areas. Mohammadian et al [30] used the effective connectivity computed with spectral dynamic causal modeling analysis to compute the information flow within RSN, finding that impaired flow and disrupted causal interaction were found in amnesic MCI and AD groups with respect to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [48] found similar results using group information-guided ICA, showing that rs-FC alterations mostly appear in the temporal, cingulate, and angular areas. Mohammadian et al [30] used the effective connectivity computed with spectral dynamic causal modeling analysis to compute the information flow within RSN, finding that impaired flow and disrupted causal interaction were found in amnesic MCI and AD groups with respect to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies on Alzheimer's disease have revealed stage-dependent brain activity fluctuations in several resting-state networks, including the default mode network (DMN), salience network (SN), dorsal attention (DAN), and limbic networks (LN) [3,6,18,22,25,33,35,38,41]. To date, only a few fMRI studies have used a whole-brain dynamic approach and showed the impact of Alzheimer's disease on brain dynamics and information processing across large-scale brain networks [30,39, 48]. This could provide a deeper understanding of how disease progression alters the underlying brain dynamics, which is critical for providing a more reliable understanding of how AD-related changes impact cognition, emotion, and behavior and for developing targeted interventions for AD-related disorders [17,45].The intrinsic ignition framework [10] presents a view of the brain as a complex system characterized by dynamical properties essential for efficient information processing.…”
mentioning
confidence: 99%
“…Brain structures implicated in the DMN mostly include the posterior cingulate cortex (PCC), precuneus cortex, medial prefrontal and lateral temporal cortices and hippocampus (Forouzannezhad et al ., 2019 ). Reduced functional connectivity in AD is shown between MTL structures, such as the hippocampus and entorhinal cortex, and the PCC by rs-fMRI (Greicius et al ., 2004 ; Mohammadian et al ., 2023 ; Yu et al ., 2017 ; Zheng et al ., 2017 ). This evidence indicates the significance of the MTL in the DMN as an indicator of AD.…”
Section: Mrimentioning
confidence: 99%
“…Higher MMSE scores show better mental capability's score of 24 following educational correction is suggested for patients with VCI (29). Five studies (24,25,26,27,28) collected MMSE scores. There was a statistically significant difference between the two groups.…”
Section: Msse Scoresmentioning
confidence: 99%
“…Higher MOCA score represents good cognitive function and a cut off of 26 following education is need for people with cognitive disorders. The MoCA score was recorded in two studies (27,28). The meta-analysis showed a statistically significant difference between the two groups.…”
Section: Moca Scoresmentioning
confidence: 99%